Sectional type sintering method for anode foil of aluminum electrolytic capacitor

The segmented sintering method for aluminum electrolytic capacitor anode foils addresses capacity and mechanical defects by two-stage sintering and quality control, improving mechanical properties and ensuring consistent quality.

CN119252669AInactive Publication Date: 2025-01-03DONGGUAN AILLEN ELECTRONICS TECH CO LTD

Patent Information

Application Number
CN202411312140.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing anode foils for aluminum electrolytic capacitors face issues with limited specific capacity growth, mechanical defects due to closed pores from solvents and binders, and quality assessment challenges during sintering, leading to inconsistent product quality.

Method used

A segmented sintering method involving two-stage sintering with controlled temperature and time, combined with precise slurry preparation and drying, to ensure proper bonding and removal of solvents and binders, accompanied by quality assessment through color difference analysis.

Benefits of technology

Enhances mechanical properties and bending performance of the sintered foil, allows for consistent quality control by identifying and correcting mixing issues, and ensures effective bonding between aluminum powder and foil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252669A_ABST
    Figure CN119252669A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of aluminum electrolytic capacitors, and particularly relates to a sectional type sintering method of an aluminum electrolytic capacitor anode foil, which comprises the steps of slurry preparation, coating, drying and sintering, when the slurry is prepared, the slurry can be fully bonded by adding a very small amount of binder, the redundant binder can be easily removed in the first stage of sintering, and a large number of tiny holes are formed in the surface of an aluminum powder layer; the tiny holes are beneficial to absorbing deformation energy when the anode foil is bent, so that cracks are reduced, the bending performance of the sintered foil is greatly enhanced, and the formed anode foil has more excellent mechanical properties; in the second stage of sintering, sufficient combination of the aluminum powder and the aluminum foil substrate is guaranteed; and meanwhile, a good sintering neck is formed between the aluminum powder and the aluminum powder, so that the aluminum sintered foil has good bending resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aluminum electrolytic capacitors, and in particular relates to a segmented sintering method for an anode foil of an aluminum electrolytic capacitor. Background Art

[0002] Aluminum electrolytic capacitors are one of the indispensable components in modern electronic products. They have excellent performance, large capacity, low cost, easy processing, and convenient use. They are widely used in important fields such as mobile phones, televisions, household appliances, power supplies, hybrid devices, and aerospace, military, etc., and play the role of filtering, bypassing, coupling and decoupling in the circuit.

[0003] Nowadays, most of the anode foils of domestic aluminum electrolytic capacitors use traditional etched foils. However, the expansion rate of traditional etched foils has approached the theoretical limit, the growth of the specific capacity of industrially formed foils has almost stagnated, and the corrosion process will produce a large amount of acidic waste liquid containing metal ions. In recent years, additive manufacturing has been introduced to replace chemical etching. This method uses spherical aluminum powder and plain aluminum foil as the main raw materials. By stacking aluminum powder layers on aluminum foil, the surface undulations of the aluminum powder layers are relied on to increase the specific surface area of ​​the anode foil.

[0004] The improvement of the specific capacitance of sintered anode foil is achieved by constructing a three-dimensional pore structure with a high specific surface area on the foil through sintering and chemical formation processes, so as to increase the surface area of ​​the electrode foil in contact with the electrolyte during operation, thereby achieving the purpose of increasing the capacitance. Therefore, it is necessary to ensure that there are a large number of connected pores between the aluminum powder particles on the foil after sintering, and at the same time, there is a certain bonding strength between the particles and between the particles and the foil, so that the sintered foil does not "fall powder" during operation, ensuring the use effect and life of the sintered foil. In the prior art, due to the presence of substances such as solvents, binders and dispersants, the anode foil will produce defects such as closed pores, which will deteriorate the mechanical properties of the sintered foil. Therefore, another function of sintering is to remove excess binder, decompose it completely, and finally leave aluminum powder that is interconnected. In addition, during sintering, if the sintering is incomplete, the sintered foil is prone to powdering; if the sintering is excessive, the aluminum sintered foil will be too hard, resulting in poor quality of the sintered foil, and it is impossible to judge the quality of the coated aluminum foil after drying. When the quality of the coated aluminum foil is unqualified, it is impossible to determine whether it is caused by a problem with the slurry layer ratio or inadequate mixing, which affects subsequent aluminum foil processing.

[0005] To this end, the present invention provides a segmented sintering method for an anode foil of an aluminum electrolytic capacitor. Summary of the invention

[0006] In order to make up for the deficiencies of the prior art, at least one technical problem raised in the background technology is solved.

[0007] The technical solution adopted by the present invention to solve the technical problem is: a segmented sintering method of an aluminum electrolytic capacitor anode foil according to the present invention comprises the following steps:

[0008] Step 1: slurry preparation: spherical aluminum powder, a binder, an organic solvent and a dispersant are placed in a ball mill, and ball milled to obtain a mixed aluminum powder slurry;

[0009] Step 2: coating, the mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of the 30 μm aluminum foil substrate by a coating machine to form an aluminum slurry layer;

[0010] Step 3: drying, placing the aluminum foil with the aluminum slurry layer after coating in step 2 in a vacuum dryer for drying to obtain a dried coated aluminum foil;

[0011] Step 4 is sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two stages: in the first stage, the temperature is raised to 240-450°C at a heating rate of 1-10°C / min, and the temperature is kept for 60-120min; in the second stage, the temperature is continued to be raised to 560-659°C at the same heating rate, and the temperature is kept for 60-480min, so as to realize the segmented sintering of the anode foil of the aluminum electrolytic capacitor.

[0012] Furthermore, during the ball milling in step 1, the ball milling speed is 250-400 rpm and the time is 3-6 hours.

[0013] Furthermore, in step 2, the thickness of the aluminum foil substrate is 10-40 μm; and the scraper speed of the coating machine is 3-5 mm / s.

[0014] Furthermore, in step 3, the vacuum drying temperature is 50-80° C. and the time is 6-12 h.

[0015] Furthermore, the atmosphere used in the sintering process in step 4 is air, argon, or a mixture of argon and hydrogen.

[0016] Furthermore, the first sintering stage in step 4 can remove the solvent, binder and dispersant substances in the sintered foil; the second sintering stage can make the aluminum powder particles melt and bond together.

[0017] Furthermore, the average particle size of the spherical aluminum powder is 1-5 μm; and the organic solvent is one or more of ethanol, ethylene glycol or terpineol.

[0018] Furthermore, the binder is one or more of carboxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinylidene fluoride or phenolic resin; the dispersant is one or more of oleic acid, polyvinyl alcohol, stearic acid or glycerol.

[0019] Furthermore, the weight ratio of spherical aluminum powder, organic solvent, binder and dispersant in the aluminum powder slurry is (55-70): (25-40): (1-4): (1-4).

[0020] Furthermore, the purity of the spherical aluminum powder is greater than 99.98%.

[0021] The beneficial effects of the present invention are as follows:

[0022] 1. The segmented sintering method of the anode foil of an aluminum electrolytic capacitor described in the present invention can make the slurry fully bonded by adding a very small amount of binder when preparing the slurry. In the first stage of sintering, the excess binder can be easily removed to form a large number of tiny holes on the surface of the aluminum powder layer. Such tiny holes help to absorb the energy of deformation when the anode foil is bent, thereby reducing cracks, greatly enhancing the bending performance of the sintered foil, and making the anode foil after chemical formation have more excellent mechanical properties. On the other hand, the final sintering state is very important to the mechanical properties of the sintered foil. Therefore, in the second stage of sintering, it is necessary to ensure that the aluminum powder and the aluminum foil substrate can be fully bonded; at the same time, a good sintering neck is formed between the aluminum powder and the aluminum powder, and the aluminum sintered foil has good bending resistance.

[0023] 2. The present invention discloses a segmented sintering method for an anode foil of an aluminum electrolytic capacitor. The method obtains the color difference values ​​of all color difference areas of the coated aluminum foil and sums them to obtain a total color difference value, which can reflect the degree of color difference of the coated aluminum foil. The ratio of the total number of color difference areas to the total number of detection areas is then obtained to obtain a color difference area proportion value, which can reflect the proportion of the overall color difference areas of the coated aluminum foil. The mixed abnormal value is obtained by combining the color difference area proportion value and the total color difference value. By comparing the mixed abnormal value with the mixed abnormal threshold value, the quality of the coated aluminum foil after drying can be judged. When the quality of the coated aluminum foil is unqualified, the reason for the unqualified quality of the coated aluminum foil can be quickly judged, which is convenient for taking corresponding treatment measures in the subsequent process to improve the subsequent processing quality of the coated aluminum foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention will be further described below in conjunction with the accompanying drawings.

[0025] Figure 1 It is a method flow chart of a segmented sintering method of an aluminum electrolytic capacitor anode foil of the present invention;

[0026] Figure 2 is a temperature control diagram of the first stage and the second stage in the process of the present invention;

[0027] Figure 3 This is a physical picture of the sintered foil and a scanning electron microscope microscopic morphology picture. DETAILED DESCRIPTION

[0028] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.

[0029] A segmented sintering method for an aluminum electrolytic capacitor anode foil comprises the following steps:

[0030] Step 1: slurry preparation: spherical aluminum powder, binder, organic solvent and dispersant are mixed evenly according to a preset mass ratio and ball-milled to form aluminum powder slurry;

[0031] Step 2: coating, the mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of the aluminum foil substrate by a coating machine to form a slurry layer;

[0032] Step 3: drying, placing the aluminum foil with the aluminum slurry layer after coating in step 2 in a vacuum dryer for drying to obtain dried coated aluminum foil; taking pictures of the dried coated aluminum foil with a high-definition camera to obtain high-definition pictures of each coated aluminum foil;

[0033] Each high-definition picture of the coated aluminum foil is divided into a number of detection areas, and the standard picture is also divided into the same number of detection areas, and the color difference value SC in the same detection area of ​​the high-definition picture and the standard picture is collected by a colorimeter; the color difference value SC is compared with the color difference value threshold value YSC; the color difference value threshold value YSC is set according to actual experience;

[0034] If the color difference value SC ≥ the color difference value threshold YSC, it indicates that the color difference between the high-definition image and the standard image of the detection area is large, indicating that the aluminum paste layer in the detection area is unevenly mixed, and the detection area is marked as a color difference area;

[0035] On the contrary, if the color difference value SC is less than the color difference value threshold value YSC, it indicates that the color difference between the high-definition image and the standard image of the detection area is small, indicating that the aluminum paste layer of the detection area is evenly mixed, and the detection area is marked as a color-free area;

[0036] Obtain the color difference values ​​SC of all color difference areas of the coated aluminum foil and sum them up to obtain the total color difference value ZS;

[0037] Get the total number of detection areas N divided by the high-definition image of the coated aluminum foil, and then get the total number of color difference areas FS. Get the percentage value ZSB of the area with color difference;

[0038] The mixed abnormality value YCZ is obtained by using the formula YCZ=ZS×a1+ZSB×a2, wherein a1 and a2 are preset proportional coefficients and a1+a2=1, and the mixed abnormality value YCZ is compared with the mixed abnormality threshold GHZ; the mixed abnormality threshold GHZ includes a first mixed abnormality threshold GHZ1 and a second mixed abnormality threshold GHZ2, and the first mixed abnormality threshold GHZ1<the second mixed abnormality threshold GHZ2;

[0039] If the mixing abnormality value YCZ ≥ the second mixing abnormality threshold GHZ2, it indicates that the slurry layer of the coated aluminum foil is not mixed evenly, and a slurry layer mixing failure signal is generated, and the slurry layer needs to be re-proportioned and mixed;

[0040] If the first mixing abnormality threshold GHZ1≤mixing abnormality value YCZ<the second mixing abnormality threshold GHZ2, it indicates that the mixing uniformity of the coated aluminum foil slurry layer barely meets the standard, and a barely meeting standard signal is generated, and the mixing time needs to be extended;

[0041] If the mixed abnormal value YCZ is less than the first mixed abnormal threshold GHZ1, it indicates that the aluminum foil coating slurry layer is mixed evenly and no operation is required;

[0042] It should be noted that the color difference value of the same detection area of ​​the high-definition image and the standard image is collected by a colorimeter. If the color difference value ≥ the color difference value threshold, it indicates that the color difference between the high-definition image and the standard image in the detection area is large, indicating that the aluminum slurry layer in the detection area is unevenly mixed. The detection area is marked as a color difference area. The color difference values ​​of all color difference areas of the coated aluminum foil are obtained and summed to obtain the total color difference value, which can reflect the degree of color difference of the coated aluminum foil; then the ratio of the total number of color difference areas to the total number of detection areas is obtained to obtain the proportion of color difference areas, which can reflect the proportion of the overall color difference areas of the coated aluminum foil; the mixed anomaly value is obtained by combining the two factors of the proportion of color difference areas and the total color difference value; the larger the mixed anomaly value, the greater the difference between the coated aluminum foil and the standard image, and the more mixed the slurry layer is. Uneven, by comparing with the mixing abnormality threshold, when the mixing abnormality value YCZ ≥ the second mixing abnormality threshold GHZ2, it indicates that the slurry layer of the coated aluminum foil is unevenly mixed. The reason for this situation is most likely that there is a problem with the proportion of the slurry layer, so a slurry layer mixing failure signal is generated, and the slurry layer needs to be re-proportioned and mixed; and when the first mixing abnormality threshold GHZ1 ≤ mixing abnormality value YCZ < the second mixing abnormality threshold GHZ2, it indicates that the mixing uniformity of the slurry layer of the coated aluminum foil barely meets the standard. This result indicates that there is no problem with the correct matching of the slurry layer, so a barely qualified signal is generated, and the standard can be met by extending the mixing time; when the mixing abnormality value YCZ < the first mixing abnormality threshold GHZ1, it indicates that the slurry layer of the coated aluminum foil is evenly mixed, no operation is required, and the next step can be directly entered;

[0043] Step 4: sintering, sintering the dried coated aluminum foil obtained in step 3; Figure 2 As shown, the sintering is specifically divided into two stages: in the first stage, the temperature is raised to 240-450°C at a heating rate of 1-10°C / min and kept warm for 60-120min; in the second stage, the temperature is continued to be raised to 560-659°C at the same heating rate and kept warm for 60-480min, thereby realizing the segmented sintering of the anode foil of the aluminum electrolytic capacitor.

[0044] When ball milling is performed in step 1, the ball milling speed is 250-400 rpm and the time is 3-6 hours.

[0045] In step 2, the thickness of the aluminum foil substrate is 10-40 μm; and the scraper speed of the coating machine is 3-5 mm / s.

[0046] In step 3, the vacuum drying temperature is 50-80° C. and the time is 6-12 hours.

[0047] The atmosphere used in the sintering process in step 4 is air, argon or a mixture of argon and hydrogen.

[0048] The first stage of sintering in step 4 can remove the solvent, binder and dispersant substances in the sintered foil; the second stage of sintering can make the aluminum powder particles melt and bond together.

[0049] The average particle size of the spherical aluminum powder is 1-5 μm; the organic solvent is one or more of ethanol, ethylene glycol or terpineol.

[0050] The binder is one or more of carboxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinylidene fluoride or phenolic resin; the dispersant is one or more of oleic acid, polyvinyl alcohol, stearic acid or glycerol.

[0051] The weight ratio of spherical aluminum powder, organic solvent, binder and dispersant in the aluminum powder slurry is (55-70): (25-40): (1-4): (1-4).

[0052] The purity of the spherical aluminum powder is greater than 99.98%.

[0053] The method flow chart of the segmented sintering method of the anode foil of the aluminum electrolytic capacitor described in the present invention is shown in Figure 1 The temperature control diagram of the first and second stages in the process of the present invention is shown in Figure 2 content.

[0054] Example 1

[0055] A segmented sintering method for an aluminum electrolytic capacitor anode foil comprises the following steps:

[0056] Step 1 Slurry preparation:

[0057] Spherical aluminum powder with an average particle size of 3 μm, a binder carboxymethyl cellulose, an organic solvent ethylene glycol, and a dispersant oleic acid are mixed in a mass ratio of 55:25:1:1, and then the mixed raw materials are put into a ball mill and ball-milled at a rotation speed of 300 rpm to obtain a slurry;

[0058] Step 2: Coating:

[0059] The mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of a 30 μm aluminum foil substrate by a coating machine, with a coating thickness of 150 μm to form a slurry layer;

[0060] Step 3 Drying:

[0061] The aluminum foil with the aluminum slurry layer after coating in step 2 is vacuum dried at 80° C. for 12 h to obtain a dried coated aluminum foil;

[0062] Step 4: sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two steps: in the first stage, the temperature is increased to 420°C at a heating rate of 5°C / min and kept warm for 120 minutes; in the second stage, the temperature is continued to be increased to 650°C at the same heating rate and kept warm for 360 minutes.

[0063] Embodiment 2:

[0064] A segmented sintering method for an aluminum electrolytic capacitor anode foil comprises the following steps:

[0065] Step 1 Slurry preparation:

[0066] Spherical aluminum powder with an average particle size of 3 μm, a binder carboxymethyl cellulose, an organic solvent ethanol, and a dispersant stearic acid are mixed in a mass ratio of 70:40:4:4, and then the mixed raw materials are put into a ball mill and ball-milled at a rotation speed of 300 rpm to obtain a slurry;

[0067] Step 2: Coating:

[0068] The mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of a 30 μm aluminum foil substrate by a coating machine, with a coating thickness of 150 μm to form a slurry layer;

[0069] Step 3 Drying:

[0070] The aluminum foil with the aluminum slurry layer after coating in step 2 is vacuum dried at 80° C. for 12 h to obtain a dried coated aluminum foil;

[0071] Step 4: sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two steps: in the first stage, the temperature is raised to 420°C at a heating rate of 4°C / min and kept at this temperature for 120 minutes; in the second stage, the temperature is further raised to 655°C at the same heating rate and kept at this temperature for 240 minutes;

[0072] Comparative Example 1:

[0073] A segmented sintering method for an aluminum electrolytic capacitor anode foil comprises the following steps:

[0074] Step 1 Slurry preparation:

[0075] Spherical aluminum powder with an average particle size of 3 μm, a binder carboxymethyl cellulose, an organic solvent ethanol, and a dispersant stearic acid are mixed in a mass ratio of 55:25:1:1, and then the mixed raw materials are put into a ball mill and ball-milled at a rotation speed of 300 rpm to obtain a slurry;

[0076] Step 2: Coating:

[0077] The mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of a 30 μm aluminum foil substrate by a coating machine, with a coating thickness of 150 μm to form a slurry layer;

[0078] Step 3 Drying:

[0079] The aluminum foil with the aluminum slurry layer after coating in step 2 is vacuum dried at 80° C. for 12 h to obtain a dried coated aluminum foil;

[0080] Step 4: sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two steps: in the first stage, the temperature is raised to 360°C at a heating rate of 5°C / min and kept at this temperature for 120 minutes; in the second stage, the temperature is further raised to 600°C at the same heating rate and kept at this temperature for 480 minutes;

[0081] Comparative Example 2:

[0082] A segmented sintering method for an aluminum electrolytic capacitor anode foil comprises the following steps:

[0083] Step 1 Slurry preparation:

[0084] Spherical aluminum powder with an average particle size of 3 μm, a binder carboxymethyl cellulose, an organic solvent ethylene glycol, and a dispersant oleic acid are mixed in a mass ratio of 70:40:4:4, and then the mixed raw materials are put into a ball mill and ball-milled at a rotation speed of 300 rpm to obtain a slurry;

[0085] Step 2: Coating:

[0086] The mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of a 30 μm aluminum foil substrate by a coating machine, with a coating thickness of 150 μm to form a slurry layer;

[0087] Step 3 Drying:

[0088] The aluminum foil with the aluminum slurry layer after coating in step 2 is vacuum dried at 80° C. for 12 h to obtain a dried coated aluminum foil;

[0089] Step 4: sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two steps: in the first stage, the temperature is raised to 360°C at a heating rate of 5°C / min and kept at this temperature for 120 minutes; in the second stage, the temperature is further raised to 655°C at the same heating rate and kept at this temperature for 480 minutes;

[0090] Comparative Example 3:

[0091] A segmented sintering method for an aluminum electrolytic capacitor anode foil comprises the following steps:

[0092] Step 1 Slurry preparation:

[0093] Spherical aluminum powder with an average particle size of 5 μm, a binder carboxymethyl cellulose, an organic solvent ethylene glycol, and a dispersant oleic acid are mixed in a mass ratio of 55:25:1:1, and then the mixed raw materials are put into a ball mill and ball-milled at a rotation speed of 300 rpm to obtain a slurry;

[0094] Step 2: Coating:

[0095] The mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of a 30 μm aluminum foil substrate by a coating machine, with a coating thickness of 150 μm to form a slurry layer;

[0096] Step 3 Drying:

[0097] The aluminum foil with the aluminum slurry layer after coating in step 2 is vacuum dried at 80° C. for 12 h to obtain a dried coated aluminum foil;

[0098] Step 4: sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two steps: in the first stage, the temperature is raised to 360°C at a heating rate of 5°C / min and kept at this temperature for 120 minutes; in the second stage, the temperature is further raised to 650°C at the same heating rate and kept at this temperature for 360 minutes;

[0099] Comparative Example 4:

[0100] A segmented sintering method for an aluminum electrolytic capacitor anode foil comprises the following steps:

[0101] Step 1 Slurry preparation:

[0102] Spherical aluminum powder with an average particle size of 5 μm, a binder carboxymethyl cellulose, an organic solvent ethylene glycol, and a dispersant oleic acid are mixed in a mass ratio of 70:40:4:4, and then the mixed raw materials are put into a ball mill and ball-milled at a rotation speed of 300 rpm to obtain a slurry;

[0103] Step 2: Coating:

[0104] The mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of a 30 μm aluminum foil substrate by a coating machine, with a coating thickness of 150 μm to form a slurry layer;

[0105] Step 3 Drying:

[0106] The aluminum foil with the aluminum slurry layer after coating in step 2 is vacuum dried at 80° C. for 12 h to obtain a dried coated aluminum foil;

[0107] Step 4: sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two steps: in the first stage, the temperature is raised to 420°C, i.e., T1, at a heating rate of 5°C / min, and kept at this temperature for 120 minutes; in the second stage, the temperature is further raised to 655°C, i.e., T2, at the same heating rate, and kept at this temperature for 480 minutes;

[0108] Comparative Example 5:

[0109] A segmented sintering method for an aluminum electrolytic capacitor anode foil comprises the following steps:

[0110] Step 1 Slurry preparation:

[0111] Spherical aluminum powder with an average particle size of 3 μm, a binder carboxymethyl cellulose, an organic solvent ethylene glycol, and a dispersant oleic acid were mixed in a mass ratio of 62:30:2:2, and then the mixed raw materials were put into a ball mill and ball-milled at a rotation speed of 300 rpm to obtain a slurry;

[0112] Step 2: Coating:

[0113] The mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of a 30 μm aluminum foil substrate by a coating machine, with a coating thickness of 150 μm to form a slurry layer;

[0114] Step 3 Drying:

[0115] The aluminum foil with the aluminum slurry layer after coating in step 2 is vacuum dried at 80° C. for 12 h to obtain a dried coated aluminum foil;

[0116] Step 4: sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two steps: in the first stage, the temperature is raised to 420°C at a heating rate of 5°C / min and kept at this temperature for 120 minutes; in the second stage, the temperature is further raised to 655°C at the same heating rate and kept at this temperature for 240 minutes;

[0117] Comparative Example 6:

[0118] A segmented sintering method for an aluminum electrolytic capacitor anode foil comprises the following steps:

[0119] Step 1 Slurry preparation:

[0120] Spherical aluminum powder with an average particle size of 5 μm, a binder carboxymethyl cellulose, an organic solvent ethylene glycol, and a dispersant oleic acid were mixed in a mass ratio of 50:20:0.5:0.5, and then the mixed raw materials were put into a ball mill and ball-milled at a rotation speed of 300 rpm to obtain a slurry;

[0121] Step 2: Coating:

[0122] The mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of a 30 μm aluminum foil substrate by a coating machine, with a coating thickness of 150 μm to form a slurry layer;

[0123] Step 3 Drying:

[0124] The aluminum foil with the aluminum slurry layer after coating in step 2 is vacuum dried at 80° C. for 12 h to obtain a dried coated aluminum foil;

[0125] Step 4: sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two steps: in the first stage, the temperature is raised to 420°C at a heating rate of 5°C / min and kept at this temperature for 120 minutes; in the second stage, the temperature is further raised to 655°C at the same heating rate and kept at this temperature for 360 minutes;

[0126] The mechanical properties of the sintered aluminum electrolytic capacitor anode foil prepared according to the method are improved compared with those of the common corrosion foil. The prepared sintered aluminum electrolytic capacitor anode foil is subjected to a metal bending mechanical property test. The metal bending mechanical property test standard can be specifically referred to YB / T5349-2006 "Metal Bending Mechanical Property Test Method". The mechanical properties of the embodiment and the comparative example are shown in Table 1 below.

[0127] Table 1: Mechanical properties test

[0128]

[0129] As shown in Table 1, by sintering in stages and adjusting the sintering temperature and time of each stage, a sintered foil with excellent bending performance can be obtained. When designing the process, the first stage of sintering must ensure that the solvent binder inside is completely removed, while the second stage must ensure that the aluminum powder and the aluminum powder and the aluminum foil base are fully bonded.

[0130] Shape detection:

[0131] The microstructure of the sintered foil of the example and comparative example products was analyzed by scanning electron microscope (SEM) to observe the bonding degree between the aluminum powder particles. Figure 3 shown.

[0132] Figure 3 The following are the physical pictures and scanning electron microscope microscopic morphology pictures of the sintered foil prepared according to the method. Figure 3 The sintered foils are shown from top to bottom as the actual pictures of Example 1, Example 2 and Comparative Example 4. The right side shows the scanning electron microscope microscopic morphology of Example 1, and a1 is the local enlarged picture of a; the scanning electron microscope microscopic morphology of Comparative Example 4, and b1 is the local enlarged picture of b. It can be seen from Examples 1 and 2 that there are no obvious cracks and breaks in the aluminum foil during the winding and flattening process, and no aluminum powder falls off. It can be seen from Comparative Example 4 that the distance between aluminum powder particles becomes shorter as the aluminum powder content increases. During the melting process of the aluminum powder surface, the aluminum solution is more likely to gather at the contact position between the particles to form a larger sintering neck.

[0133] Application examples:

[0134] A segmented sintering method for an aluminum electrolytic capacitor anode foil comprises the following steps:

[0135] Step 1 Slurry preparation:

[0136] Spherical aluminum powder with an average particle size of 3 μm, a binder carboxymethyl cellulose, an organic solvent ethylene glycol, and a dispersant oleic acid are mixed in a mass ratio of 55:25:1:1, and then the mixed raw materials are put into a ball mill and ball-milled at a rotation speed of 300 rpm to obtain a slurry;

[0137] Step 2: Coating:

[0138] The mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of a 30 μm aluminum foil substrate by a coating machine, with a coating thickness of 150 μm to form a slurry layer;

[0139] Step 3 Drying:

[0140] The aluminum foil with the aluminum slurry layer after coating in step 2 is vacuum dried at 80° C. for 12 hours to obtain a dried coated aluminum foil; a high-definition camera is used to take pictures of the dried coated aluminum foil to obtain a high-definition picture of each coated aluminum foil;

[0141] Each high-definition picture of the coated aluminum foil is divided into a number of detection areas, and the standard picture is also divided into the same number of detection areas, and the color difference value SC in the same detection area of ​​the high-definition picture and the standard picture is collected by a colorimeter; the color difference value SC is compared with the color difference value threshold value YSC; the color difference value threshold value YSC is set according to actual experience;

[0142] If the color difference value SC ≥ the color difference value threshold YSC, it indicates that the color difference between the high-definition image and the standard image of the detection area is large, indicating that the aluminum paste layer in the detection area is unevenly mixed, and the detection area is marked as a color difference area;

[0143] On the contrary, if the color difference value SC is less than the color difference value threshold value YSC, it indicates that the color difference between the high-definition image and the standard image of the detection area is small, indicating that the aluminum paste layer of the detection area is evenly mixed, and the detection area is marked as a color-free area;

[0144] Obtain the color difference values ​​SC of all color difference areas of the coated aluminum foil and sum them up to obtain the total color difference value ZS;

[0145] Get the total number of detection areas N divided by the high-definition image of the coated aluminum foil, and then get the total number of color difference areas FS. Get the percentage value ZSB of the area with color difference;

[0146] The mixed abnormality value YCZ is obtained by using the formula YCZ=ZS×a1+ZSB×a2, wherein a1 and a2 are preset proportional coefficients and a1+a2=1, and the mixed abnormality value YCZ is compared with the mixed abnormality threshold GHZ; the mixed abnormality threshold GHZ includes a first mixed abnormality threshold GHZ1 and a second mixed abnormality threshold GHZ2, and the first mixed abnormality threshold GHZ1<the second mixed abnormality threshold GHZ2;

[0147] If the mixing abnormality value YCZ ≥ the second mixing abnormality threshold GHZ2, it indicates that the slurry layer of the coated aluminum foil is not mixed evenly, and a slurry layer mixing failure signal is generated, and the slurry layer needs to be re-proportioned and mixed;

[0148] If the first mixing abnormality threshold GHZ1≤mixing abnormality value YCZ<the second mixing abnormality threshold GHZ2, it indicates that the mixing uniformity of the coated aluminum foil slurry layer barely meets the standard, and a barely meeting standard signal is generated, and the mixing time needs to be extended;

[0149] If the mixed abnormal value YCZ is less than the first mixed abnormal threshold GHZ1, it indicates that the aluminum foil coating slurry layer is mixed evenly and no operation is required;

[0150] It should be noted that the color difference value of the same detection area of ​​the high-definition image and the standard image is collected by a colorimeter. If the color difference value ≥ the color difference value threshold, it indicates that the color difference between the high-definition image and the standard image in the detection area is large, indicating that the aluminum slurry layer in the detection area is unevenly mixed. The detection area is marked as a color difference area. The color difference values ​​of all color difference areas of the coated aluminum foil are obtained and summed to obtain the total color difference value, which can reflect the degree of color difference of the coated aluminum foil; then the ratio of the total number of color difference areas to the total number of detection areas is obtained to obtain the proportion of color difference areas, which can reflect the proportion of the overall color difference areas of the coated aluminum foil; the mixed anomaly value is obtained by combining the two factors of the proportion of color difference areas and the total color difference value; the larger the mixed anomaly value, the greater the difference between the coated aluminum foil and the standard image, and the more mixed the slurry layer is. Uneven, by comparing with the mixing abnormality threshold, when the mixing abnormality value YCZ ≥ the second mixing abnormality threshold GHZ2, it indicates that the slurry layer of the coated aluminum foil is unevenly mixed. The reason for this situation is most likely that there is a problem with the proportion of the slurry layer, so a slurry layer mixing failure signal is generated, and the slurry layer needs to be re-proportioned and mixed; and when the first mixing abnormality threshold GHZ1 ≤ mixing abnormality value YCZ < the second mixing abnormality threshold GHZ2, it indicates that the mixing uniformity of the slurry layer of the coated aluminum foil barely meets the standard. This result indicates that there is no problem with the correct matching of the slurry layer, so a barely qualified signal is generated, and the standard can be met by extending the mixing time; when the mixing abnormality value YCZ < the first mixing abnormality threshold GHZ1, it indicates that the slurry layer of the coated aluminum foil is evenly mixed, no operation is required, and the next step can be directly entered;

[0151] Step 4: sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two steps: in the first stage, the temperature is increased to 420°C at a heating rate of 5°C / min and kept warm for 120 minutes; in the second stage, the temperature is continued to be increased to 650°C at the same heating rate and kept warm for 360 minutes.

[0152] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A segmented sintering method for an aluminum electrolytic capacitor anode foil, characterized in that: The following steps are involved: Step 1: slurry preparation: spherical aluminum powder, a binder, an organic solvent and a dispersant are placed in a ball mill, and ball milled to obtain a mixed aluminum powder slurry; Step 2: coating, the mixed aluminum powder slurry obtained in step 1 is evenly coated on the front and back sides of the aluminum foil substrate by a coating machine to form an aluminum slurry layer; Step 3: drying, placing the aluminum foil with the aluminum slurry layer after coating in step 2 in a vacuum dryer for drying to obtain a dried coated aluminum foil; Step 4 is sintering, sintering the dried coated aluminum foil obtained in step 3; the sintering is specifically divided into two stages: in the first stage, the temperature is raised to 240-450°C at a heating rate of 1-10°C / min, and the temperature is kept for 60-120min; in the second stage, the temperature is continued to be raised to 560-659°C at the same heating rate, and the temperature is kept for 60-480min, so as to realize the segmented sintering of the anode foil of the aluminum electrolytic capacitor.

2. The segmented sintering method of the anode foil of an aluminum electrolytic capacitor according to claim 1, characterized in that: When ball milling is performed in step 1, the ball milling speed is 250-400 rpm and the time is 3-6 hours.

3. The segmented sintering method of the anode foil of an aluminum electrolytic capacitor according to claim 1, characterized in that: In step 2, the thickness of the aluminum foil substrate is 10-40 μm; and the scraper speed of the coating machine is 3-5 mm / s.

4. The segmented sintering method of the anode foil of an aluminum electrolytic capacitor according to claim 1, characterized in that: In step 3, the vacuum drying temperature is 50-80° C. and the time is 6-12 hours.

5. The segmented sintering method of the anode foil of an aluminum electrolytic capacitor according to claim 1, characterized in that: The atmosphere used in the sintering process in step 4 is air, argon or a mixture of argon and hydrogen.

6. The segmented sintering method of the anode foil of an aluminum electrolytic capacitor according to claim 1, characterized in that: In the step 4, the organic solvent, binder and dispersant in the sintered foil are removed in the first sintering stage; and the aluminum powder particles are melted and bonded together in the second sintering stage.

7. The segmented sintering method of the anode foil of an aluminum electrolytic capacitor according to claim 1, characterized in that: The average particle size of the spherical aluminum powder is 1-5 μm; the organic solvent is one or more of ethanol, ethylene glycol or terpineol.

8. The segmented sintering method of the anode foil of an aluminum electrolytic capacitor according to claim 1, characterized in that: The binder is one or more of carboxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinylidene fluoride or phenolic resin; the dispersant is one or more of oleic acid, polyvinyl alcohol, stearic acid or glycerol.

9. The segmented sintering method of the anode foil of an aluminum electrolytic capacitor according to claim 1, characterized in that: The weight ratio of spherical aluminum powder, organic solvent, binder and dispersant in the aluminum powder slurry is (55-70): (25-40): (1-4): (1-4).

10. The segmented sintering method of the anode foil of an aluminum electrolytic capacitor according to claim 1, characterized in that: The purity of the spherical aluminum powder is greater than 99.98%.

Citation Information

Patent Citations

  • Pole piece coating method

    CN101577327A

  • Detection method for dispersion uniformity of battery electrode sizing agent and application

    CN108287171A

  • Method, system and device for detecting color difference based on machine vision and storage medium

    CN109141640A

  • Sintered aluminum electrolytic capacitor low-voltage anode foil and preparation method thereof

    CN111146005A

  • Method for analyzing distribution form of SBS modifier in asphalt mixture

    CN111307767A

Cited By

  • Preparation method of aluminum powder sintered foil based on thermal expansion coefficient adaptation

    CN122025423A